Geospatial Modeling of Blue Carbon Ecosystem Coastal Degradation in Jakarta Bay - Nasir Sudirman; Muhammad Helmi; Hadiwijaya L. Salim (Indonesian Journal of Oceanography, 2019)
Jakarta Bay is shallow water which is used for various activities, currently experiencing environment, soil,and sediment degradation. Jakarta Bay experienced rapid development, population growth, increased economic activity and utilization of coastal resources. The development of Jakarta Bay is carried out to balance land necessity and overcome the problem of land subsidence through reclamation and construction of sea dikes. Ecosystem services arethe contribution of various interrelated ecological structures and functions, mangrove ecosystems provide services as an important part of the carbon cycle. Mangroves use CO2 for photosynthesis and store it in Biomass and sediment stock. Mangrove ecosystems in Jakarta Bay have been degraded and deforested due to land conversion for settlement, facilities, and other activities, in line with the increasing population. The calculation of the service value of mangrove ecosystems is limited to economic valuation and descriptive account, geospatial modelling has not been widely carried out, this has caused widespread and temporal unknown data on ecosystem services. The Coastal Blue Carbon geospatial modelling used in this study requires land use classification data input based on the interpretation of Landsat satellite's images and global carbon deposits in mangrove ecosystems while carbon prices are based on Social Cost Carbon (SCC), Greenhouse Gas Initiative (RGGI) and International Voluntary Market Price (IVMP). This study produced a map of the dynamics of carbon stock, sequestration, emissions, accumulation and net present value of carbon. The output of these maps is expected to be a referencefor sustainable mangrove management, coastal area planning optimization with mangrove ecosystem protection so it can be part of climate change mitigation efforts in Jakarta Bay.